2020
DOI: 10.3390/cancers12051197
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA HOTAIR in Breast Cancer Therapy

Abstract: Breast cancer (BC) is the most common cancer type among women, and morbidity and mortality rates are still very high. Despite new innovative therapeutic approaches for all BC molecular subtypes, the discovery of new molecular biomarkers involved in tumor progression has been fundamental for the implementation of personalized treatment strategies and improvement of patient management. Many experimental studies indicate that long non-coding RNAs (lncRNAs) are strongly involved in BC initiation, metastatic progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 163 publications
0
55
0
Order By: Relevance
“…Although numerous studies have highlighted the crucial role of HOTAIR in several physiological cellular processes, indicating it as a cell cycle-related gene [ 38 ], most experimental observations are oriented to understanding its role in tumorigenesis [ 29 ]. In fact, the overexpression of HOTAIR has been related to the evolution of some solid cancers [ 26 , 39 , 40 ] with a crucial role in cancer initiation, progression, and drug sensibility modulation [ 41 , 42 ].…”
Section: Hotair and Its Role In Cancermentioning
confidence: 99%
“…Although numerous studies have highlighted the crucial role of HOTAIR in several physiological cellular processes, indicating it as a cell cycle-related gene [ 38 ], most experimental observations are oriented to understanding its role in tumorigenesis [ 29 ]. In fact, the overexpression of HOTAIR has been related to the evolution of some solid cancers [ 26 , 39 , 40 ] with a crucial role in cancer initiation, progression, and drug sensibility modulation [ 41 , 42 ].…”
Section: Hotair and Its Role In Cancermentioning
confidence: 99%
“…The activity of pro-survival factors, including Akt, ERK, and BCL-2, is also diminished by the downregulation of lncRNA-HOTAIR [ 257 , 258 ]. The oncogenic function of lncRNA-HOTAIR can be exerted by direct or indirect suppression of several tumor-suppressive miRNAs, such as miR-7, miR-34, miR-126, and miR-206 [ 259 , 260 ]. Consistent with these findings, it was demonstrated that lncRNA-HOTAIR promotes the anoikis resistance, anchorage-independent growth, and peritoneal/liver metastasis of gastric cancer cells [ 245 , 246 ] ( Figure 3 and Table 3 ).…”
Section: Long Noncoding Rnas Anoikis and Anchorage-independent Gmentioning
confidence: 99%
“…Tumor cells present a number of characteristics, such as self-proliferation ability [ 2 ], apoptosis resistance [ 3 ], unlimited replication potential [ 4 ], insensitivity to growth inhibition [ 5 ], continuous angiogenesis [ 6 ], tissue invasion [ 7 ] and metastasis [ 8 ]. Mammary tumorigenesis is a multistep process involving activation of oncogenes or inactivation of tumor suppressors, abnormal expression of noncoding RNA [ 9 ], loss of genome stability [ 10 ] and various genetic and epigenetic alterations [ 11 ]. Tumor cells prefer glycolysis for glucose metabolism under aerobic conditions (Warburg effect) rather than mitochondrial oxidative phosphorylation, which is more efficient for ATP production so that tumor cells can produce more energy and various metabolites in a short period of time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%